Computer-based collaborative revision as a virtual lab of translation genetics - Scocchera, Giovanna (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
Introducing revision as a key stage of any writing process, including translation, this paper aims at underlining its role in the genetics of translation. Other-revision, i.e. the activity performed by a reviser on someone else’s translation, will be the focus of this paper, whose overall objective is to show that when performed in a collaborative modality, revision may prove a miniature, virtual lab of translation genetics. With the aid of computer tools already available, and new ad-hoc solutions hopefully to be developed, all reviser-translator interplay in the form of text changes, suggestions and comments can be visually tracked, recorded and thus become an object of study. Besides being an invaluable didactic tool and a hoped-for professional practice, computer-based collaborative revision may prove a valid method for data elicitation and collection, and for experimental investigation in the field of translation genetics.